Macronutrient Fertility on Irrigated Corn/Soybean in Rotation - Eric Adee (Kansas Agricultural Experiment Station Research Reports, 2025)
Effects of nitrogen (N), phosphorus (P), and potassium (K) fertilization on a corn/ soybean cropping sequence were evaluated from 2015 to 2023 (corn planted in odd years) from a study initiated in 1983. Corn yields responded most to N, followed by P fertilization, and soybean yields were most influenced by P fertilization. The highest return on fertilizer investment averaged over both crops was when N, P, and K were more closely meeting the needs of the crops.
Keywords: macronutrients; corn yield